Pengaruh Tingkat Pendidikan Terhadap Kesempatan Berkarir (Studi Kasus Pada Masyarakat Kabupaten Batang) - Mohammad Zacky (Sahmiyya, 2023)
Education and career are two things that are interrelated in an effort to improve one's quality of life. This research was conducted to gain a deeper understanding of this relationship, as well as provide a solution to the problem of inequality in career opportunities for people with low education. In addition, this research also has important value for the development of government policies and programs in the field of education and workforce in Batang Regency, so that it is hoped that it can improve the quality of education and community career opportunities. Thus, this research can make a positive contribution to social and economic development in Batang Regency and the surrounding area. The research method used by researchers is in the form of qualitative research. A qualitative research method is a research method that uses descriptive data in the form of written or spoken language from observable people and actors. This qualitative approach is used to explain and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs, and perceptions. Based on the results of the research conducted, there is a significant positive relationship between education level and career opportunities in Batang Regency. This can be seen from the data which shows that the higher a person's education level, the greater the opportunity to get a good job and have better career opportunities. in Batang Regency